Clinical Characteristics of Patients With Coronavirus Disease 2019 in Japan: A Single-Center Case Series. (8th May 2020) - Kobayashi, Ken-ichiro; Kaki, Takahiro; Mizuno, Shinsuke; Kubo, Kenji; Komiya, Nobuhiro; Otsu, Satoko
Abstract: We report a case series of 6 patients with confirmed coronavirus disease 2019 (COVID-19) in Wakayama prefecture, Japan. All 6 of the patients tested positive via pharyngeal swab polymerase chain reaction (PCR) tests, and 2 of the 6 were still positive at 3 weeks after onset. All of the patients exhibited bilateral ground glass opacities on computed tomography (CT). This article also reports narrative information on the spectrum of symptoms collected directly from the patients. It would be difficult to triage patients with COVID-19 based on the typical symptoms of fever and/or cough, although PCR and CT are definitive in diagnosis. Abstract : We report a case series of 6 patients with COVID-19. The complaints and symptoms experienced by the patients varied. It would be difficult to triage patients with COVID-19 based on typical symptoms, although polymerase chain reaction and computed tomography are definitive in diagnosis.